Variação sazonal da composição corporal de lagartos teiús (Salvator merianae) utilizando a técnica não invasiva Absorciometria de Raios-X de Dupla Energia (DEXA) - Carabolante, Tiago Fabricio (Universidade Federal de São Carlos, 2022)
The significant reproductive investment in spring, preceded by metabolic and activity reduction during winter hibernation and followed by high summer activity in Salvator merianae, must be accompanied by important changes in protein, lipid and bone mineral body composition. Non-invasive techniques for measuring body composition are essential for longitudinal studies of life history, and the relationship between body condition and physiology, in addition to the consequent reduction in the number of experimental animals. Dual energy X-ray absorptiometry (DEXA) is a non-invasive measurement technique that provides values of bone mineral content, lean mass and fat mass. This technique is widely used to determine the body composition of humans, as well as other mammals and birds, but its use in lizards is poorly understood, requiring validation. Therefore, the objectives of this study were: i) to validate the use of the DEXA technique, from the comparison with direct chemical analysis, to measure each component of the body composition of S. merianae lizards; ii) to determine the seasonal variation of the body composition of S. merianae from DEXA scans repeated in each season of the year. Our results show a strong correlation between the values obtained by the predictive mathematical models and values observed in the chemical analysis (r values between 0.95 and 0.99) without significant differences between the means. The results indicate changes related to the use of lipid energy reserves to meet the reproductive demand in males and females, with possible recruitment of bone calcium sources by females in egg production. Therefore, we conclude that the DEXA technique presents itself as a potential and excellent tool for measuring the body composition of tegu lizards, enabling the construction of mathematical models with high predictive power for body components and highly related to the life history of the species. With the successful validation and application in a study of seasonal variation, the use of DEXA seems to be very promising in the performance of longitudinal studies that evaluate patterns in the variation of body composition that are related to morphophysiological and bioenergetic changes, in addition to knowledge about the ecology and the life history of the species.
Seasonal variation of body composition of tegu lizards (Salvator merianae) using the non-invasive technique Dual Energy X-ray Absorptiometry (DEXA)
Keywords: Massa de gordura; Massa de proteína; Massa mineral óssea; Validação metodológica; Machos; Fêmeas; Fat mass; Protein mass; Bone mineral mass; Methodological validation; Males; Females; CIENCIAS BIOLOGICAS::FISIOLOGIA